MODEL ELEMEN HINGGA UNTUK MASALAH INKLUSI DUA DIMENSI - Tanjung, Jafril
Laboratory experiments in concrete indicated that addition of sound aggregates into a mix cement-sand matrix, increases its Compressive Strength and Modulus of Elasticity. Bentur's investigation in the field of High Strength Concrete concluded that the condition of the interface layer, i.e. a very thin layer surrounding the aggregates, affects the compressive strength significantly. Beside, it is general knowledge that many other parameters, such as water cement ratio, type of cement, curing method, aggregates size, quality of aggregates, etc., affect the ultimate strength of concrete in many different ways. To explore the mechanical background of such intriguing phenomena in a detail fashion, a series of investigation involving fundamental principles if felt necessary. A simplifying approach to the problem is adopted, by first keeping several parameters constant and leave the ones of interest free to vary. Here interest is cast on the influence of the size of aggregates on the ultimate strength of concrete specimens. For the above purpose, planar test specimens of High Strength Mortar is prepared, pain as well as with cylindrical metal implants if varying diameters. These specimens were subjected to compression test for their crushing strength, load deflection relation and this mode of failure. Base on acquired test data, a Non Linear Finite Element Computer Program based on eight nodes isoparametric element is prepared to simulate the behavior of the specimens. This program is expected to represent the physical phenomena observed. in the Laboratory, covering the elastic as well as the non elastic domain. For predicting the post peak deformation branch of loaddeflection response curve of specimens, a computational procedure based on displacement increments approach of Non Linear Finite Element Method using a secant stiffness approach is employed. The predictions of the Finite Element Model are compared with the available experimental data, and the comparisons are judged good, covering the predicting the post peak deformation branch of load-deflection response curve as well as to represent the mode of failure of the specimens.